Fast-Growing Wood-Polymer Nano Composite Characteristics through Nano-SiO2 Impregnation - Istie Rahayu; Abdul Salam Min Rohmatillah; Esti Prihatini; Wayan Darmawan; Gilang Dwi Laksono; Vera Junita Sitanggang (Wood Research Journal, 2022)
Ganitri (Elaeocarpus sphaericus (Gaertn.) K. Schum.) and jabon (Anthocephalus cadamba) are fast-growing wood species that have low strength and durability class. One of methods for improving the characteristics of ganitri and jabon woods is impregnation. This study objectives were to analyze the effect of impregnation of Melamine Formaldehyde Furfuryl Alcohol (MFFA) copolymer and 0.5% Nano-SiO2 on the physical, mechanical and durability properties of ganitri and jabon woods. The impregnation process was carried out by applying a 0.5 bar vacuum for 1 hour and followed by 2 bar pressure for 2 hours. The results showed that impregnation with MFFA and Nano-SiO2 could improve optimally the physical and mechanical properties and durability of fast-growing woods